Proton-Gated Rectification Regimes in Nanofluidic Diodes Switched by Chemical Effectors - Pérez Mitta, Gonzalo (2018)
During the last decade, nanofluidic devices based on solid-state nanopores and nanochannels have come into scene in materials science and will not leave anytime soon. One of the main reasons for this is the excellent control over ionic transport exerted by such devices that promises further important advances when integrated into more complex molecular devices. As a result, pH, temperature, and voltage-regulated devices have been obtained. However, nowadays, there is still a necessity for molecule-driven nanofluidic devices. Here, a sugar-regulated pH-responsive nanofluidic diode is presented obtained by surface modification of conical polycarbonate nanochannels with electropolymerized 3-aminophenylboronic acid. Control over the ionic transport has been achieved by a successful decoration of asymmetric nanochannels with integrated molecular systems. The as-synthesized boronate-appended zwitterionic polymer exhibits an acid-base equilibrium that depends on the concentration of sugar, which ultimately acts as a chemical effector setting different pH-dependent rectification regimes. As a result, the same nanodevice can perform completely different proton-regulated nanofluidic operations, i.e., anion-driven rectification, cation-driven rectification, and no rectification, by simply varying the concentration of fructose in the electrolyte solution.